Competency maturing: a substantive theory of how senior information systems undergraduates develop their existing competencies and acquire additional competencies within an organic learning environment - Ogundipe, Tejumade V (Department of Information Systems, 2022)
There is a high demand for competent Information Systems (IS) / Information Technology (IT) graduates in a globalised knowledge-driven economy with rapidly evolving Information and Communication Technology (ICT). However, becoming a competent IS/IT graduate is not a once-off event because rapid technological changes require that IS/IT graduates continually strive to be up-to-date and relevant. Continuous updating of knowledge, keeping up-to-date, acquiring a diverse set of IS/IT/ICT competencies, and being competent is a problematic task globally, and requires building competencies comprising knowledge, skills, abilities and values. This thesis employs Classic Grounded Theory Methodology (CGTM) with a single case to identify the main concern of senior IS undergraduates during their learning process, and how they resolve the concern. Data were obtained from two diverse groups of senior IS undergraduate classes using multiple data collection methods, embedded in constant comparative analyses. Understanding what was going on in the substantive research area and explaining how the senior IS undergraduates' main concern was resolved was the focus of the data collection and conceptualisation. Through the single case exploratory CGTM study, the senior IS undergraduates' main concern emerged as a perceived lack of IS Competency, and the main concern was explored. A substantive theory of Competency Maturing conceptualises and explains how these students attempt to resolve their perceived lack of IS Competency. A substantive theory of Competency Maturing is a Basic Social Process (BSP) which involves engaging in learning by doing, and spontaneous learning within an organic learning environment. Three phases of the BSP of Competency Maturing are student engagement, self-awareness of competency, and self-development. This thesis recommends a Framework for a South African senior IS undergraduates' programme and offers a set of conceptual propositions developed from empirical data. The thesis makes theoretical and practical contributions to the IS education body of knowledge of student engagement, learning environment, senior IS undergraduates' curriculum development and competency development. A substantive theory of Competency Maturing is relevant to IS educators who wish to break away from traditional, teacher-centred approaches in higher education, and are willing to create learning environments where senior IS undergraduates are motivated to learn in rich, relevant and real-world contexts. The thesis contributes to IS educators who seek to understand how the learning environment and IS educational content influence and support student engagement and Competency Maturing. This thesis also offers IS educational practitioners an understanding of the educational content and a delivery style that can provide senior IS undergraduates with strong theoretical and practical foundations. The thesis's findings suggest that creating an organic learning environment can be a useful approach to developing more competent IS graduates.